Anesthetic Care of 2 Siblings With Neonatal Ichthyosis and Sclerosing Cholangitis Syndrome: Case Reports. Issue 8 (15th October 2018) - Khalifa, Céline; Boliaki Botombe, Geoffrey; Stephenne, Xavier; Veyckemans, Francis
Abstract : We report for the first time the anesthetic management of 2 sisters suffering from neonatal ichthyosis and sclerosing cholangitis syndrome. They both presented with neonatal cholestatic jaundice and ichthyosis. The first was admitted for orthotopic liver transplantation at the age of 1 year, and the second patient underwent open pyeloplasty for a pyeloureteric junction syndrome at the age of 4 years. These 2 case reports highlight that, except for the potential difficulties with securing the catheters, dressings and endotracheal tube to the skin, the anesthetic implications of neonatal ichthyosis and sclerosing cholangitis syndrome are mainly related to the liver disease: cirrhosis and portal hypertension.